2018
DOI: 10.1097/coc.0000000000000359
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Concurrent Medication Use on Pancreatic Cancer Survival—SEER-Medicare Analysis

Abstract: In this study, use of β-blockers, heparin, insulin, and warfarin were associated with improved survival in patients with pancreatic cancer. Additional studies are needed to validate these findings in the clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 43 publications
2
29
0
Order By: Relevance
“…No clear rate differences were observed by β-blocker receptor selectivity owing to very few patients on NSBB. A SEER-Medicare analysis also showed improved survival in patients with PDAC on β-blocker therapy (Beg et al, 2017). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No clear rate differences were observed by β-blocker receptor selectivity owing to very few patients on NSBB. A SEER-Medicare analysis also showed improved survival in patients with PDAC on β-blocker therapy (Beg et al, 2017). …”
Section: Discussionmentioning
confidence: 99%
“…In addition, cancer mortality is significantly increased by high levels of psychological stress (Batty et al, 2017). On the other hand, it is suggested that β-blocker treatment of patients suffering from colorectal cancer (Jansen et al, 2014), breast cancer (Barron et al, 2011), ovarian cancer (Watkins et al, 2015), melanoma (Lemeshow et al, 2011), and PDAC (Beg et al, 2017; Udumyan et al, 2017), may lead to improved survival.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the pooling analysis by Zhang et al indicated that metformin may improve the survival for cancer patients with concurrent diabetes, particularly for breast, colorectal, ovarian, and endometrial cancer, but they failed to show such survival benefit in pancreatic cancer with only 3 studies included (HR=0.80, 95% CI= 0.62-1.03) [14]. Additionally, a recent meta-analysis combining 27 studies comprising 24178 participants was conducted to qualify the adjuvant effect of metformin in cancers, suggesting a better survival, particularly in colorectal and prostate cancer, however without special attention to pancreatic cancer Reni,2016 [26] Italy ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ 8 Lee,2016 [27] Korea ▲ ▲ ▲ ▲ ▲ ▲ ▲ 7 Ambe,2016 [21] USA ▲ ▲ ▲ ▲ ▲ ▲ 6 Cheon,2014 [28] Korea ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ 8 Hwang,2013 [29] USA ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ 9 Amin,2016 [30] USA ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ 8 Kordes,2015 [31] Netherlands ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ 9 Chaiteerakij,2016 [32] USA ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ 8 Sadeghi,2012 [33] USA ▲ ▲ ▲ ▲ ▲ ▲ 6 Cerullo,2016 [34] USA ▲ ▲ ▲ ▲ ▲ ▲ ▲ 7 Kozak,2016 [35] USA ▲ ▲ ▲ ▲ ▲ ▲ ▲ 7 Toomey,2015 [36] USA ▲ ▲ ▲ ▲ ▲ 5 Choi,2015 [37] Korea ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ 8 Beg,2017 [38] USA ▲ ▲ ▲ ▲ ▲ ▲ ▲ 7 Jang,2017 [39] Korea ▲ ▲ ▲ ▲ ▲ ▲ ▲ ▲ 8 Frouws,2017 [40] Netherlands ▲ ▲ ▲ ▲ ▲ ▲ ▲ 7 E,2017 [41] USA ▲ ▲ ▲ ▲ ▲ ▲ ▲ 7 [46] and by E et al (6 studies with 12,057 participants) have represented similar findings with demonstrating a survival benefit of metformin therapy for pancreatic cancer patients [47]. Furthermore, the subgroup analyses based on ethnicity in the current study revealed a more favorable prognosis for metformin therapy in Asian population (HR=0.74, P=0.01) but not evident in Caucasian population (HR= 0.92, P=0.10) which was in line with the findings by Zhou et al, indicating that ethnicity variation may contribute to the metformin action, however, the underlying mechanism for the discrepancy remains undefined.…”
Section: Discussionmentioning
confidence: 99%
“…However encouraging the results from experimental studies may be, the role of beta-blockers in cancer patients remains unclear and the results from mostly retrospective observational studies are equivocal. There are studies suggesting the use of beta-blockers may be able to prolong survival of cancer patients [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]. On the other hand, there are also studies that do not support such a hypothesis [50][51][52][53][54][55][56][57][58][59][60].…”
Section: Discussionmentioning
confidence: 99%